PENERAPAN MODEL PEMBELAJARAN AUDITORY INTELECTUALY REPETITION (AIR) BERBANTUAN MEDIA PUZZLE UNTUK MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIKA SISWA KELAS IV UPTD SD NEGERI 50 PAREPARE - Rahmadani, Annesya; Natriani Syam; Ila Israwaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The survey carried out in UPTD SD Negeri 50 was motivated by the level of students' learning activity, which still needs to be improved. The objective of this study is to determine the level of students' learning activity by applying the Auditory, Intellect, Repetitive (AIR) learning model supported by puzzle teaching materials to mathematics subjects. The survey uses a qualitative approach, a type of face-to-face survey carried out in three phases. The results based on the collected data show that the introduction of the Auditory, Intellect, Repetitive Learning (AIR) model improves students' learning and efficiency, with the teacher's effectiveness reaching the highest category at 72.2% in the first cycle, while the student's learning efficiency reached the medium category at 58%, while in the second phase, the teacher's effectiveness was in the high category at 88% and the student's learning effectiveness reached the average category at . The teacher's effectiveness in the third phase was in the high category at 100% and the student's learning effectiveness was in the high category at 91.6%. Therefore, it is proposed to apply the UPTD SD Negeri 50 Parepare IV Auditory, Intellectual and Repetitive (AIR) learning model, which can be concluded to improve the learning process and activities of mathematics subjects in first grade students.